2022
DOI: 10.1136/annrheumdis-2021-221957
|View full text |Cite
|
Sign up to set email alerts
|

Low dose, add-on prednisolone in patients with rheumatoid arthritis aged 65+: the pragmatic randomised, double-blind placebo-controlled GLORIA trial

Abstract: BackgroundLow-dose glucocorticoid (GC) therapy is widely used in rheumatoid arthritis (RA) but the balance of benefit and harm is still unclear.MethodsThe GLORIA (Glucocorticoid LOw-dose in RheumatoId Arthritis) pragmatic double-blind randomised trial compared 2 years of prednisolone, 5 mg/day, to placebo in patients aged 65+ with active RA. We allowed all cotreatments except long-term open label GC and minimised exclusion criteria, tailored to seniors. Benefit outcomes included disease activity (disease activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
1
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 46 publications
1
78
1
5
Order By: Relevance
“…These findings also need to be viewed in light of the improved prognosis of current RA patients; the extent of damage at initial presentation and progression of such damage have strongly decreased over the last 2 decades, as the authors document in their discussion. This was confirmed in the GLORIA trial, in which it was observed that damage progression in 2 years was 0.3 units in the prednisolone group and 1.9 in the placebo group (10), similar to the rates in the Krause trial.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…These findings also need to be viewed in light of the improved prognosis of current RA patients; the extent of damage at initial presentation and progression of such damage have strongly decreased over the last 2 decades, as the authors document in their discussion. This was confirmed in the GLORIA trial, in which it was observed that damage progression in 2 years was 0.3 units in the prednisolone group and 1.9 in the placebo group (10), similar to the rates in the Krause trial.…”
supporting
confidence: 66%
“…This included trials that continued therapy for up to 2 years. Very recently, the pragmatic Glucocorticoid Low‐dose Outcome in Rheumatoid Arthritis (GLORIA) trial compared the results of 2 years of prednisolone (5 mg/day) or placebo added to optimized standard care in senior patients with established RA (disease duration ≥11 years, age ≥65 years) (10). Even at this low dose, prednisolone reduced disease activity and joint damage progression, with the tradeoff of a 24% increased risk of an AE of special interest, mostly nonsevere infections.…”
Section: Figurementioning
confidence: 99%
“…Although many modern RA treatment strategies aim for GC free remission, GC remain important therapeutics in rheumatoid arthritis, particularly when given short-term and early in the course of the disease. The effects of low-dose GC may be much less deleterious than the effects of chronic high dose GC treatment and indeed a recently published randomized controlled trial on Glucocorticoid LOw-dose in RheumatoId Arthritis (GLORIA) [15] demonstrated no statistical difference in symptomatic fracture rates between patients with established RA treated with 5 mg of Prednisolone or placebo. Further bone health outcomes demonstrated a small but significant lumbar spine BMD loss (-1%) in the Prednisolone group but no differences in hip BMD change between the Prednisolone and placebo group after a mean treatment time of 19 months.…”
Section: Conventional Synthetic Dmardsmentioning
confidence: 99%
“…Das Gleichgewicht zwischen Nutzen und Risiken ist noch unklar, insbesondere für chronisch niedrig dosierte GC-Therapien. Um diese Frage zu beantworten, wurde die internationale, 1: 1 randomisierte, Placebo-kontrollierte 2-Jahres-Studie GLO-RIA (Glucocorticoid LOw-dose in RheumatoId Arthritis) durchgeführt [6].…”
Section: Hintergrundunclassified